DERMATOPHYTOSIS IN A TERTIARY CARE HOSPITAL: A CLINICO-MYCOLOGICAL STUDY - Vijender Kumar (Journal of Biomedical and Pharmaceutical Research, 2018)
BACKGROUND A fungal infection of the skin, hair, and nails is called dermatophytosis. It has been a major issue for national public health during the last few years. Studies from various geographical areas have produced diverse patterns of the disease’s etiological distribution. Fungi called dermatophytes attack the skin, hair, and nails. There have been described more than a hundred species of these hyaline septate molds. Only 42 of them are accepted as legitimate, and fewer than half of them are linked to human diseases. Infections caused by this, known as dermatophytoses, are widespread in humid tropical and subtropical regions of the country. A fairly frequent superficial fungal infection found in tropical and subtropical regions is dermatophytosis. Its chronicity is caused by patient noncompliance and decreased medication responsiveness. Mycological research and antifungal sensitivity testing are essential given the rise in antifungal resistance and occurrence. AIM: The aim of this study was to evaluate the host-related factors of chronic dermatophytosis and to identify the common fungal isolates. MATERIAL AND METHOD: This was an observational study carried out in a tertiary care hospital’s dermatology department. Dermatophytosis was identified clinically. All patients were required to sign written informed consent forms. The study involved 50 dermatophytic infection patients who were seen in the dermatology outpatient department of a tertiary hospital. A thorough history was taken, followed by a clinical examination. A thorough history of the patients’ age, sex, occupation, site of the lesion, and related illnesses was obtained, and patients underwent clinical examinations to determine the nature and location of the lesion. The patient was informed of the technique before the sample was taken. The patient underwent a thorough general, physical, systemic, and cutaneous examination. RESULTS: 50 clinically confirmed cases of dermatophytosis served as the basis for the current study’s isolation, identification, and clinicomycological analysis of dermatophytes. These 50 samples included 34 (68%) skin scrapings, 9 (18%) nail clippings, and 7 (14%) hair stubs. Males made up 40% (20 cases) of the 50 clinically confirmed instances of dermatophytoses, while females made up 60% (30 cases). The age range of 11 to 20 years had the highest number of instances. 50 cases of dermatophytoses were examined, and 36 (72%) of those cases had positive direct microscopy results whereas 14 (28%) did not. Only 23 of the 36 wet mount positive cases had cultures that grew; the remaining 13 did not. Three samples produced dermatophyte isolates from among the 14 wet mount negative cases. CONCLUSION: Dermatophytosis is a minor illness with expensive treatment costs and psychological side effects. Infections with dermatophytes are particularly prevalent in our nation, where the hot, humid weather combined with unfavorable hygienic conditions encourages the growth of these fungus. Tinea corporis and tinea cruris were the two clinical types of Dermatophytes that were most prevalent. In different regions of India, distinct species are more or less isolated from one another. But in the majority of the experiments, Trichophyton was the main fungus. These fungi infections can be prevented with the use of good hygiene, sanitation, and washing. KEYWORDS: Dermatophytosis, Dermatophytes, Tinea, Trichophyton, Lactophenol Cotton Blue, Tinea and Antifungal